Own the A.I. revolution : unlock your artificial intelligence strategy to disrupt your competition - Sahota, Neil; Ashley, Michael (McGraw-Hill, 2019)
"The definitive primer on A.I., from one of today's leading experts, that empowers business leaders to leverage the potential of AI to disrupt themselves now to gain a competitive advantage"--